Molecular Network Analysis Reveals Transmission of HIV-1 Drug-Resistant Strains Among Newly Diagnosed HIV-1 Infections in a Moderately HIV Endemic City in China - Zhao, Bin; Song, Wei; Kang, Mingming; Dong, Xue; Li, Xin; Wang, Lu; Liu, Jianmin; Ding, Haibo; Chu, Zhenxing; Wang, Lin; Qiu, Yu; Shang, Hong; et al. (Frontiers in Microbiology, 2022)
Since the implementation of the “treat all” policy in China in 2016, there have been no data on the prevalence of transmitted drug resistance (TDR) in China. In this study we describe TDR in patients newly diagnosed with human immunodeficiency virus (HIV) infection between 2016 to 2019 in Shenyang city, China. Demographic information and plasma samples from all newly reported HIV-infected individuals in Shenyang from 2016 to 2019 were collected. The HIV pol gene was amplified and sequenced for subtyping and TDR. The spread of TDR was analyzed by inferring an HIV molecular network based on pairwise genetic distance. In total, 2882 sequences including CRF01_AE (2019/2882, 70.0%), CRF07_BC (526/2882, 18.3%), subtype B (132/2882, 4.6%), and other subtypes (205/2882, 7.1%) were obtained. The overall prevalence of TDR was 9.1% (95% confidence interval [CI]: 8.1%–10.2%), with the highest prevalence observed in CRF07_BC (14.6% [95% CI:11.7%–18.0%], CRF01_AE (7.9% [95% CI: 6.7%–9.1%], p<0.0001), subtype B (9.1% [95% CI: 4.8%–15.3%], p=0.0990), and other sequences (7.3% [95% CI: 4.2%–11.8%], p=0.0066). TDR mutations detected in more than 10 cases were Q58E (n=51), M46ILV (n=46), K103N (n=26), E138AGKQ (n=25), K103R/V179D (n=20), and A98G (n=12). Molecular network analysis revealed three CRF07_BC clusters with TDR (two with Q58E [29/29] and one with K103N [10/19]); and five CRF01_AE clusters with TDR (two with M46L [6/6], one with A98G [4/4], one with E138A [3/3], and one with K103R/V179D [3/3]). In the TDR clusters, 96.4% (53/55) of individuals were men who have sex with men (MSM). These results indicate that TDR is moderately prevalent in Shenyang (5%–15%) and that TDR strains are mainly transmitted among MSM, providing precise targets for interventions in China.